2017
DOI: 10.1371/journal.pone.0179774
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of West Nile Virus in Israel: A nationwide cross sectional study

Abstract: West Nile Virus (WNV) is endemic in Israel, affecting yearly 40–160 individuals. Israel is located on a central migratory path between Africa and Eurasia and most West Nile Fever (WNF) cases reported in recent years were among residents of the coastal plain. The aim of the study was to evaluate the seroprevalence of WNV among the Israeli population and to assess correlates for WNV infection. A cross-sectional nationwide serologic survey was conducted using 3,145 serum samples collected by the national Israeli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
3
21
1
Order By: Relevance
“…Therefore, men are more exposed to potential mosquito bites and getting infected because they spend most of the daytime outdoors. Recent studies have been shown a relationship between WNV prevalence and gender [43, 44]. Consistent with our results, there are no significant differences between living in rural or urban areas, because there is no lifestyle disparities between these two populations in this region of the country.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, men are more exposed to potential mosquito bites and getting infected because they spend most of the daytime outdoors. Recent studies have been shown a relationship between WNV prevalence and gender [43, 44]. Consistent with our results, there are no significant differences between living in rural or urban areas, because there is no lifestyle disparities between these two populations in this region of the country.…”
Section: Discussionsupporting
confidence: 91%
“…The multivariate analysis revealed an increase of SINV seroprevalence with age (Table 2 and Table 3). Several studies have previously similarly demonstrated that seroprevalence is higher with age, both for SINV [21] and for other vector-borne viral diseases such as WNV [17]. This observation fits very well with what we know about vector-borne viruses, i.e., the longer time a person is exposed, the higher the chances of encountering mosquitoes carrying SINV and as a result, the more frequent the infection with SINV.…”
Section: Discussionsupporting
confidence: 83%
“…According to our study, the prevalence of IgG antibodies against SINV in the Israeli population in 2011–2014 was 3.6% as determined by ELISA assay and 1.9% as determined by SINV NT assay. The discrepancy between the results from ELISA and neutralization assays for arboviral diagnosis is not new and was already demonstrated by us and others for WNV [17,18,19,20]. Since our study measured SINV seroprevalence in the general population, it is much more likely that many of the SINV-positive persons were infected several years ago and therefore had lower levels of IgG which could be enough for detection by ELISA but not to neutralize the virus.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Following the 2000 outbreak, a national mosquito surveillance system was established which is responsible for entomological analysis of mosquitoes and characterization of WNV circulation in Israel ( Orshan et al, 2008 ; Lustig et al, 2015 ). Furthermore, WNV infections in humans and seropositivity of the population are monitored routinely and are integrated with mosquito surveillance data by the public health division to assess the burden of WNV circulation in Israel and implement appropriate measures ( Lustig et al, 2015 , 2017a , b ; Bassal et al, 2017 ). Recently, the public health and veterinary services, Israel Nature and Park Authorities and the ministry of environmental protection have initiated a program to integrate WNV data obtained from humans, mosquitos, horses, and birds with the aim to develop a true one health initiative for WNV in Israel.…”
Section: Wnv Surveillance Within the One Health Initiativementioning
confidence: 99%